Fe-bearing magnesium silicate glasses for potential supplementary cementitious applications - Jiang, Chuqing; Santos, Hellen Silva; Yliniemi, Juho; Lindén, Johan; Ramteke, D. D.; Illikainen, Mirja; Cheeseman, Christopher; Kinnunen, Paivo (Frontiers in Materials, 2024)
Supplementary cementitious materials (SCMs) are used to minimize CO2 emissions associated with cement production. However, their global supply is insufficient to meet the growing market demand for cement and concrete, being essential to develop alternative SCMs based on abundant waste streams and low-cost resources. Fe-bearing Mg-based glasses are promising candidates with the potential to utilize high-volume feedstocks rich in Fe and Mg, but their effectiveness relies on deep understanding of the relationship between glass composition, reactivity, and pozzolanic properties. In this study, Fe-Mg silicate glasses with varying Fe concentrations were precisely engineered through a sol-gel route to better understand the impact of Fe on the glass structure and reactivity. While Fe3+ typically acts as a glass network former, it was observed to also function as an intermediate cation, behaving either as a network former or modifier. Glass reactivity was assessed through aqueous dissolution tests, revealing that the composition and chemical environment of Fe3+ within the glass network significantly influence the dissolution behavior. The introduction of Fe into Mg-Si glasses increased overall reactivity, potentially due to Fe-induced phase separation and the increasing of [FeO6] octahedra sites at higher Fe concentrations, which was also associated to network depolymerization. These findings deepen the understanding of the role of Fe3+ in magnesium silicate glasses, provide key insights into optimizing glass reactivity by fine-tuning the composition, and indicate the potential of these glasses as promising SCMs.